?TRACE ELEMENT STUDIES IN UROLITHIASIS; PRELIMINARY INVESTIGATION ON MIXED CALCIUM OXALATE-STRUVITE URINARY CALCULI (Biological Sciences - PJSIR, 1999)
In this study, the levels of the trace elements copper, zinc, lead, iron, aluminium, nickel, chromium along with magnesium, sodium and potassium were estimated in fifteen mixed calcium oxalate-struvite (CaOxiSTR) urinary stones. The mean values of the combined results were, copper 4.24, zinc 1302.10, lead 23.25, iron 36.48, aluminium 28.83, nickel 0.69, chromium 1.93, magnesium 4530441, sodium 54.13 and potassium 5.93 ng mg·l . It was observed that zinc, aluminium and potassium levels were higher than in.calcium oxalate (CaOx) calculi 0.05 ;; P> 0.02 and potassium levels were higher than in mixed calcium oxalate-hydroxyapatite (CaOxi APA)calculi, P